2021
DOI: 10.1002/cam4.3729
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in colorectal cancer screening among breast and prostate cancer survivors

Abstract: Background Colorectal cancer (CRC) screening is recommended as an integral part of cancer survivorship care. We compared the rates of CRC screening among breast and prostate cancer survivors by primary cancer type, patient, and geographic characteristics in a community‐based health‐care system with a mix of large and small metro urban areas. Materials and Methods Data for this retrospective study were abstracted from medical records of a multi‐specialty practice serving about 250,000 individuals in southern Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 36 publications
(62 reference statements)
3
14
0
Order By: Relevance
“…Also, over half of breast cancer survivors received recommended screening for CRC (65%) [ 31 ]. However, our data reports higher level of CRC screening utilization in breast and prostate cancer survivors compared to 44.2% of breast and 54.1% of prostate cancer survivors who had a colonoscopy screening in a multi-specialty practice [ 22 ]. This difference may be attributed to study design and population sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, over half of breast cancer survivors received recommended screening for CRC (65%) [ 31 ]. However, our data reports higher level of CRC screening utilization in breast and prostate cancer survivors compared to 44.2% of breast and 54.1% of prostate cancer survivors who had a colonoscopy screening in a multi-specialty practice [ 22 ]. This difference may be attributed to study design and population sample.…”
Section: Discussionmentioning
confidence: 99%
“…To date, much research regarding CRC screening among cancer survivors predominantly focuses on breast cancer [ 18 20 ] or CRC survivors (i.e., reoccurrence of CRC) [ 21 ]. A US study reported that 54% of prostate cancer survivors and 44% of breast cancer survivors received a colonoscopy [ 22 ]. Another study among Singaporean patients reported 46% and 54% of cancer survivors underwent FOBT and colonoscopy, respectively [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that a large proportion of EC patients are cured, preventing second cancers is an important target for this population. Several studies have demonstrated low levels of colon cancer screening utilization among cancer survivors [19,20], placing greater risk for the development of second cancer when the diagnosis of LS is missed. Patients with LS have up to a 50% chance of developing a second primary cancer [21] with colorectal cancer being the most common.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer, a multifaceted, multi-mechanistic and life-threatening disease, is one of the appalling scourges worldwide. Cancer cells are characterized by uncontrollable proliferation, unstoppable differentiation and unpredictable migration [ 1 , 2 , 3 ]. Modern medicine has made great progress in the diagnosis and treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%